Oscillations of Viscoelastic Mechanical Systems with Finite Freedom - Kurbonovich, Esanov Nuriddin; Mukhamadiyevich, Saipnazarov Jonibek (Karshi Multidisciplinary International Scientific Journal, 2025)
The study investigates the natural and externally excited oscillations of viscoelastic mechanical systems possessing a finite number of degrees of freedom. Based on Lagrange’s second-order equations, the dynamical model of systems with dissipation was derived. Particular attention is paid to periodic as well as transient forced vibrations in multi-degree-of-freedom structures. The system of equations of motion is written in matrix form relative to the Matrix-column The characteristic parameters were found, where and are real numbers called damping coefficients. The attenuation decrement ratio was also determined. Non-stationary oscillations of mechanical systems are solved by the Fourier transform method.